1997
DOI: 10.1161/01.cir.96.10.3499
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Catheter Ablation of Postinfarction Ventricular Tachycardia

Abstract: In patients with well-tolerated VT, RF catheter ablation may be useful as a primary cure if no other ventricular arrhythmias are inducible on follow-up testing. Ablation of all hemodynamically tolerated arrhythmias should be attempted in patients with multiple inducible VT morphologies because of the high rate of recurrence of unablated VTs in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(33 citation statements)
references
References 36 publications
2
30
1
Order By: Relevance
“…The acute ablation success rate is similar to the results of previous larger series of patients, who underwent catheter ablation of postinfarction sustained monomorphic VT 4,5,7 . In these series acute success of ablation procedure, which was around 70%, included both the patients, in whom none targeted VT morphology was inducible at the end of the study, as well as patients with modified, but still inducible VT.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The acute ablation success rate is similar to the results of previous larger series of patients, who underwent catheter ablation of postinfarction sustained monomorphic VT 4,5,7 . In these series acute success of ablation procedure, which was around 70%, included both the patients, in whom none targeted VT morphology was inducible at the end of the study, as well as patients with modified, but still inducible VT.…”
Section: Discussionsupporting
confidence: 84%
“…As amiodarone may suppress other VT morphologies than that aimed with catheter ablation, it seems wise to continue the amiodarone therapy unless ICD is implanted 5 . Patients with modified or complex arrhythmogenic substrate, who have other rapid nonclinical VT morphologies inducible after successful elimination of clinical VT should probably receive ICD, which is supported by observation of almost 50% VT recurrences during the follow-up period in this subset of patients 4 . One patient with recent myocardial infarction deteriorated hemodynamically as a result of continuing ischemia not suitable for repeated revascularization and of incessant polymorphic VT with multiple discharges from ICD a day for the last three months.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…These areas are identified by the recording of presystolic electrograms during tachycardia. [1][2][3][4][5][6] Human studies have demonstrated that these slow-conduction areas take place in narrow bundles of viable tissue that function as conducting channels (CCs) bounded by scarred tissue. 7,8 Those CCs that are located in the endocardium are identified during tachycardia.…”
mentioning
confidence: 99%